2009
DOI: 10.1016/j.jmwh.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Midwives as Educators of Medical Students and Residents: Results of A National Survey

Abstract: This descriptive study explores the roles and responsibilities of midwives involved in teaching medical students and residents. Surveys were received from 74 academic midwifery practices in the United States that are formally involved in medical education (66% response rate). These practices employ 547 midwives. Most of these midwives have >5 years of experience as clinicians (97%) and average >5 years of experience in medical education (73%). Academic midwifery practices teach multiple learners including obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…In this study 176 of the nurse-midwives’ reported they were normally involved in medical student education 5 . A more recent American study building on the earlier study, with responses from 74 midwifery practices, found the majority taught residents and medical students as well as midwifery students 6 . Some midwives’ reported that they did not take midwifery students because of medical teaching obligations.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study 176 of the nurse-midwives’ reported they were normally involved in medical student education 5 . A more recent American study building on the earlier study, with responses from 74 midwifery practices, found the majority taught residents and medical students as well as midwifery students 6 . Some midwives’ reported that they did not take midwifery students because of medical teaching obligations.…”
Section: Introductionmentioning
confidence: 75%
“…Where legal responsibility lies in this situation needs careful consideration and is clearly an area where further exploration could be undertaken to ensure accountability is appropriately acknowledged and visible.These factors suggest the need to examine how the teaching of essential knowledge in the clinical environment is organised within the multidisciplinary team. In midwifery, it has been reported that midwives’ preceptor medical students at the expense of midwifery students 6 . There may also be conflicts between informal medical education needs and pressure to educate nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Women and Infants' Hospital Institutional Review Board approval was obtained before the surveys were mailed. The survey tool for this study was mailed to potential participants in the same envelope with a separate survey assessing midwifery involvement in medical education 1 . Stamped self‐addressed envelopes to return the surveys were included.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty years ago, a survey of the leadership role of academic midwifery directors involved in practices that participate in medical education would have yielded few responses. However, in the last 10 to 15 years, there has been a rapid expansion of this type of midwifery practice in both the United States and the United Kingdom 1–4 . This paradigm of academic midwifery practice involving medical education has not only become a fast‐growing model, but has blossomed in many settings, albeit with varied characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A 1998 survey of midwifery involvement in medical education 8 and two recent surveys 9,10 confirm the extensive involvement of midwives in medical education. Although many institutions provide triage services and teach residents, the purpose of this article is twofold: 1) to present four models of resident education in obstetric triage with midwives as faculty consultants, and 2) to explore common trends in the expanded midwifery teaching role as it relates to resident education in the triage setting.…”
Section: Introductionmentioning
confidence: 96%